Alcohol Screening and Brief Intervention in Police Custody Suites: Pilot Cluster Randomised Controlled Trial (AcCePT). (8th June 2018) - Addison, Michelle; Mcgovern, Ruth; Angus, Colin; Becker, Frauke; Brennan, Alan; Brown, Heather; Coulton, Simon; Crowe, Lisa; Gilvarry, Eilish; Hickman, Matthew; Howel, Denise; Mccoll, Elaine; et al.
Abstract : We achieved target recruitment and high brief intervention delivery if this occurred immediately after screening. Low rates of return for counselling and retention at follow-up were challenges for a definitive trial. Conversely, high consent rates for access to police data suggested at least some outcomes could be measured remotely. Abstract: Aims: There is a clear association between alcohol use and offending behaviour and significant police time is spent on alcohol-related incidents. This study aimed to test the feasibility of a trial of screening and brief intervention in police custody suites to reduce heavy drinking and re-offending behaviour. Short summary: We achieved target recruitment and high brief intervention delivery if this occurred immediately after screening. Low rates of return for counselling and retention at follow-up were challenges for a definitive trial. Conversely, high consent rates for access to police data suggested at least some outcomes could be measured remotely. Methods: A three-armed pilot Cluster Randomised Controlled Trial with an embedded qualitative interview-based process evaluation to explore acceptability issues in six police custody suites (north east and south west of the UK). Interventions included: 1. Screening only (Controls), 2. 10 min Brief Advice 3. Brief Advice plus 20 min of brief Counselling. Results: Of 3330 arrestees approached: 2228 were eligible for screening (67%) and 720 consented (32%); 386 (54%) scored 8+ on AUDIT; and 205 (53%) were enroled (79 controls, 65 brief advice and 61 brief counselling). Follow-up rates at 6 and 12 months were 29% and 26%, respectively. However, routinely collected re-offending data were obtained for 193 (94%) participants. Indices of deprivation data were calculated for 184 (90%) participants; 37.6% of these resided in the 20% most deprived areas of UK. Qualitative data showed that all arrestees reported awareness that participation was voluntary, that the trial was separate from police work, and the majority said trial procedures were acceptable. Conclusion: Despite hitting target recruitment and same-day brief intervention delivery, a future trial of alcohol screening and brief intervention in a police custody setting would only be feasible if routinely collected re-offending and health data were used for outcome measurement. Trial registration: ISRCTN number: 89291046.